1981
DOI: 10.1039/c39810000507
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cinnamolide and polygodial

Abstract: Starting from 2,6,6-trimethyl-1-vinylcyclohex-1-ene a short synthesis of the sesquiterpenes cinnamolide and polygodial has been achieved with 60% and 57% overall yields, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The brown solution was triturated by the addition of light petroleum (10 ml) and filtered through a pad of Celite. Removal of the solvent under reduced pressure gave an oil which was chromatographed on silica gel H to give ( a ) polygodial (2) (12.5 Preparation of 5,5a,6,7,8,9,9a,9b-Octahydro-6,6,9a-trimethyl-5aa,9af3,9bf3-naphtho [ 1,2-c]juran-l(3H)-one (Drimenin) (4).-To a solution of the diol (24) (0.22 g, 0.92 mmol) in D M F (25 ml) at 0 "C under argon was added t-butyldimethylsilyl chloride (166 mg, 1.1 equiv.) and imidazole (125 mg, 2 equiv.)…”
Section: I586mentioning
confidence: 99%
“…The brown solution was triturated by the addition of light petroleum (10 ml) and filtered through a pad of Celite. Removal of the solvent under reduced pressure gave an oil which was chromatographed on silica gel H to give ( a ) polygodial (2) (12.5 Preparation of 5,5a,6,7,8,9,9a,9b-Octahydro-6,6,9a-trimethyl-5aa,9af3,9bf3-naphtho [ 1,2-c]juran-l(3H)-one (Drimenin) (4).-To a solution of the diol (24) (0.22 g, 0.92 mmol) in D M F (25 ml) at 0 "C under argon was added t-butyldimethylsilyl chloride (166 mg, 1.1 equiv.) and imidazole (125 mg, 2 equiv.)…”
Section: I586mentioning
confidence: 99%
“…Lactols occur in many natural products as subunits and also serve as useful intermediates for organic synthesis. Although diols are ordinary synthetic precursors of lactols, conventional oxidations frequently undergo over‐oxidation to lactones, except for several reactions 48. We expected that (NO)Ru‐salen‐catalyzed aerobic oxidation of diols would yield the corresponding lactols predominantly because lactols are secondary alcohols in nature and should remain intact as described above.…”
Section: Chemoselective Aerobic Oxidation Of Diols To Lactolsmentioning
confidence: 99%
“…The nonasymmetric Diels−Alder (DA) reaction approaches to 1 using diene 5 (Scheme ) with various dienophiles involved in the use of harsh conditions. For example, high pressures and/or strong Lewis acids, high temperatures, or dienophiles containing two electron-withdrawing groups have been found necessary to effect a successful DA reaction. , Mayelvaganan et al reported the use of AlCl 3 in nonasymmetric Lewis acid catalyzed DA reactions of diene 5 with cis -substituted dienophiles; however, no other milder aluminum Lewis acids were mentioned in the paper …”
mentioning
confidence: 99%
“…Given that chiral 1,3-oxazolidin-2-ones act as excellent auxiliaries in asymmetric DA reactions,we began our investigation with the trans -substituted dienophile 9 that contained ( S -3a- cis )-(−)-3,3a,8,8a-tetrahydro-2 H -indeno-[1,2-d]oxazolidin-2-one as the chiral entity. Treatment of a mixture of 5 and 9 with 1.4 equiv of MeAlCl 2 at −25 °C for 8 h provided a 2:1 mixture of two compounds (Table , entry 1) in which the major compound 10 crystrallized from hexanes. The X-ray crystal structure of 10 (Figure ) indicated the major product from the DA reaction with 9 was the exo isomer.…”
mentioning
confidence: 99%